Traditional authority, customary law and accountability within CAMPFIRE in Zimbabwe - Mapedza, Everisto D. (2008)
Colonial governments 'invented' tradition in order to serve their interests in Africa. This made traditional institutions pivotal in the resilience and perpetuation of colonial rule. In Zimbabwe, the postcolonial state is in the process of 're-inventing' its subordinate version of traditional authority, which has enhanced its support base at the time its legitimacy is increasingly being questioned. This paper looks at how the year 2000 re configuration of traditional leadership impacted on customary law and democratic governance in rural Zimbabwe. It particularly explores how this is reflected within the sphere of natural resource management. It will demonstrate how the reconfiguration of traditional authority in Zimbabwe has undermined the accountability and legitimacy of traditional authorities in the north-western parts of Zimbabwe. This is being done through selectively appealing to the past in order to legitimate current practices - despite the historical contradictions. The Zimbabwean context further demonstrates that this legitimating process is based on two grounds. Firstly, the state wants the rural citizens to accept their oppressive version of traditional authorities. Their legitimacy is said to be unquestionable since it is based on an 'established tradition.' Secondly, the oppressive state policies are getting de jure recognition through passing of legislation - mainly the Traditional Leaders Act of 1998. This attribute is peculiar to the Zimbabwean state's determination to hide the oppressive state policies beneath the veneer of 'acting within the law' albeit it's arbitrary implementation. Chiefs are now largely viewed as localized state despots who are helping reproduce the postcolonial state whilst undermining their local credibility.